I wonder why planes have wings : and other questions about transport - Maynard, Christopher (Danbury, Connecticut : Grolier Inc, 1999)
With information and quirky facts to explain everything from 'Why do cars need petrol?' to 'Why do ships sink?'.
Includes index
Keywords: Transportation